Guía de exportación de mangostino a Canadá (2021)
In recent years there has been a very good economic opening in the international fruit and vegetable market, which is why producers have proposed to market in markets outside the country. In order to provide information for large and small mangosteen producers, this export guide was made, the mangosteen is a fruit classified as exotic and desired in the world thanks to its nutritional content. Throughout the specialization, knowledge and tools have been acquired that allowed the development of this guide, seeing business opportunities in the foreign market, understanding and taking advantage of the benefits of commercial agreements. All this in order to develop and specify an international business idea with current figures so that it can be used by anyone who wishes to enter the international market.